Retinoic Acid Receptor-Related Orphan Receptors: Critical Roles in Tumorigenesis - Fan, Jinshuo; Lv, Zhilei; Yang, Guanghai; Liao, Ting ting; Xu, Juanjuan; Wu, Feng; Huang, Qi; Guo, Mengfei; Hu, Guorong; Zhou, Mei; Duan, Limin; Liu, Shuqing; et al. (Frontiers in Immunology, 2018)
Retinoic acid receptor-related orphan receptors (RORs) include RORα (NR1F1), RORβ (NR1F2) and RORγ (NR1F3). These receptors are reported to activate transcription through ligand-dependent interactions with co-regulators and are involved in the development of secondary lymphoid tissues, autoimmune diseases, inflammatory diseases, the circadian rhythm and metabolism homeostasis. Researches on RORs contributing to cancer related processes have been growing and they provide evidence that RORs are likely to be considered as potential therapeutic targets in many cancers. RORα has been identified as a potential therapeutic target for breast cancer and has been investigated in melanoma, colorectal colon cancer and gastric cancer. RORβis mainly expressed in the central nervous system, but it has also been studied in pharyngeal cancer, uterine leiomyosarcoma and colorectal cancer, in addition to neuroblastoma, and recent studies suggest that RORγ is involved in various cancers, including lymphoma, melanoma and lung cancer. Some studies found RORγ to be upregulated in cancer tissues compared to normal tissues, while others indicated the opposite results. With respect to the mechanisms of RORs in cancer, previous studies on the regulatory mechanisms of RORs in cancer were mostly focused on immune cells and cytokines, but lately there have been investigations concentrating on RORs themselves. Thus, the current review summarizes reports on the regulation of RORs in cancer and highlights potential therapeutic targets in cancer.